Choice of pension scheme and job mobility in Britain - Richard Disney; Carl Emmerson (Institute for Fiscal Studies (IFS), 2002)
This paper examines the choice of pension scheme and job mobility in Britain. Workers in Britain can choose to belong wholly to the social security (public pension) programme, or to a company-provided plan (occupational pension), or to purchase their own individual pension. We use household panel data for the 1990s to show that individuals that subsequently move job select pension arrangements that a priori impose lower costs on job mobility. A feature of the British policy `experiment', and of the data, is that we can differentiate between choice of actual pension arrangement by the individual and what pension arrangements were offered to that individual. This permits us to test indirectly whether the observed relationship arises from employer selection or from pension scheme design.
Keywords: H55; J32; J63; 330; Pensions; Job tenure; labour mobility; Alterssicherung; Betriebliche Altersversorgung; Gesetzliche Rentenversicherung; Private Rentenversicherung; Arbeitsmobilität; Großbritannien